Design of a Web-Based Inventory Control Information System on Jami' Baitul Muttaqin Mosque - Mahfud, Imam; Yasin, Verdi; Junaedi, Ifan; Zulhalim, Zulhalim; Hartawan, Rumadi (Jurnal Teknologi Informatika dan Komputer, 2025)
The definition of inventory according to the Big Indonesian General Dictionary is (a list of) items used in an office, company, and inventory is the making or compilation of a list of items in an office, house, ship. imagine how complicated it would be if we wanted to find out what items were purchased by an institution in the past 05 or 10 years if we had to open files or records regarding these items in a book, perhaps more than one large stack of books would have to be we read them one by one and it will take quite a long time. In modern times like now, if these manual things are still done, we will be increasingly left behind by other people and will not be able to progress because we will lose in the competition. Fast, precise and effective work has become the main requirement for completing work in the current era of globalization. The inventory data collection application is an application that is used to control inventory items and planned expenditure. This application is designed to improve the performance of the DKM Jami' Baitul Mutaqqin Mosque, because up to now the process has been carried out manually so the time required is more long time to approve replacement of inventory items that must be replaced. This application was built using the PHP programming language and uses a MySQL database.